Nurses, formerly incarcerated adults, and Gadamer: phronesis and the Socratic dialectic. (27th February 2014) - Marlow, Elizabeth; Nosek, Marcianna; Lee, Yema; Young, Earthy; Bautista, Alejandra; Hansen, Finn Thorbjørn
Abstract This paper describes the first phase of an ongoing education and research project guided by three main intentions: (1) to create opportunities for phronesis in the classroom; (2) to develop new understandings about phronesis as it relates to nursing care generally and to caring for specific groups, like formerly incarcerated adults; and (3) to provide an opportunity for formerly incarcerated adults and graduate nursing students to participate in a dialectical conversation about ethical knowing. Gadamer's writings on practical philosophy, phronesis, and the Socratic dialectic provide the philosophical foundation and framework for the project. The first phase in the project was a 4‐h class within a graduate‐level health promotion course during which 30 nursing students and three formerly incarcerated panelists engaged in a dialectic conversation about what it means to care for formerly incarcerated adults in a meaningful way. After the class, two focus groups were conducted, one with the students and one with the formerly incarcerated panelists. Findings articulated participants' prejudices and assumptions prior to the class, expanded sense of phronesis, and ability to consider nursing practice within a larger ethical framework. Panelists and students left the class with a deeper understanding of one another and expressed an openness towards continued dialectic conversations together. Use of the Socratic dialectic within nursing curricula reflects a current and critical trend in nursing education to bring non‐epistemologic forms of knowledge into the classroom.